2022
DOI: 10.1101/2022.12.28.522105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenetic endemism of the world’s seed plants

Abstract: Assessing phylogenetic endemism, i.e., the distribution of geographically restricted and evolutionarily unique species, is key to understanding biogeographic patterns and processes and critical for global conservation planning. Here, we quantified the geographic distribution and drivers of phylogenetic endemism for ~320,000 seed plants worldwide and identified centers and drivers of evolutionarily young (neoendemism) and evolutionarily old endemism (paleoendemism). Tropical and subtropical islands of the South… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…visible overall trend of SR decrease was apparent from the southwest towards the northeast in Poland. This trend generally corresponds with the continental pattern of vascular plant SR in Europe(Mutke & Barthlott, 2005;Araújo et al, 2005;Cai et al, 2022; Fig 1a).…”
supporting
confidence: 70%
“…visible overall trend of SR decrease was apparent from the southwest towards the northeast in Poland. This trend generally corresponds with the continental pattern of vascular plant SR in Europe(Mutke & Barthlott, 2005;Araújo et al, 2005;Cai et al, 2022; Fig 1a).…”
supporting
confidence: 70%
“…In this study, we investigated the effect of climate change on the potentially climatically suitable area of plant species native to the Canary Islands, an archipelago renowned for its exceptional plant endemism (Cai et al, 2022; Fernández‐Palacios & Whittaker, 2008). As hypothesised, we found that single‐island endemic species that currently occur in predominantly arid regions would have the highest losses of climatically suitable area.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the effect of climate change on the potentially climatically suitable area of plant species native to the Canary Islands, an archipelago renowned for its exceptional plant endemism (Cai et al, 2022;Fernández-Palacios & Whittaker, 2008).…”
Section: Discussionmentioning
confidence: 99%